Evaluación de glucosa sanguínea a perros de razas pequeñas en la Zona Rural del Cantón Puebloviejo - Jiménez Jiménez, Lady Elizabeth (2024)
The canine population is increasing every year and there are more and more dogs, and there is even a higher percentage of those who are homeless than those who have a home. At the national level, according to the MSP in 2013, a total of 1,765,744 companion dogs and 263,520 felines were obtained, without taking into consideration stray dogs. On the other hand, to determine if the canine has glycemia, there are reference values to determine hypoglycemia, normoglycemia and hyperglycemia. To determine the presence of glycemia in dogs, there are reference values for each one, obtaining according to Morales (2022), hypoglycemia is equal to or less than 60 mg / dl, normoglycemia of 70 - 100 mg / dl and hyperglycemia greater than 100 mg / dl. In addition, it is worth mentioning that food is a fundamental part of the animal's metabolism, therefore, it must have a balanced diet. In general, these problems are more common in dogs from rural areas, because they eat leftovers from their owners' food. However, it also varies according to the breed, sex and age of the animal, where females are more prone than males, on the contrary, in case of age, adults tend to be obese because their metabolism is slower and accumulates fat; and puppies are prone to suffer from hypoglycemia, because they are very active animals, that is to say, very playful and glucose is the source of energy for the animal, therefore they need constant feeding. In the present investigation of 50 sampled dogs, the following results were obtained: the glucose level has an average of 80.18; in general, 14% have hypoglycemia; 70% normal glycemia and 16% hyperglycemia; In age, the lowest value is 111.67 mg/dl (3 months) and 58 mg/dl (3 and 15 years); the average glucose level is 78.21 mg/dl (49%) female and 82 mg/dl (51) males; the French breed distribution was obtained at 36% and the mixed breed and Beagle at 12%; and in body condition, 64% is ideal and 14% is thin.